Scintigraphic Detection of Experimental Myocardial Infarction with 99mTc-2,3-Dimercaptosuccinic Acid - Duška, F.; Novák, J.; Mazurová, Y.; Kubíček, J.; Yižd’a, J.; Kafka, P.; Veverková, O. (Nuklearmedizin - NuclearMedicine, 1984)
Acute myocardial infarctions were produced by ligature of the left frontal descending coronary artery in 9 dogs. The possibility of scintigraphic imaging with 99mTc-DMSA 4 hrs after intravenous administration was studied. The infarctions were 4, 24 and 48 hrs old. The in vivo scan was positive in only one dog with a 4-hr old infarction. The in vivo scans were confirmed by the analysis of the radioactivity in tissue samples. The accumulation of the radiopharmaceutical increased slightly in 48-hr old lesions; however, this increase was not sufficient for a positive scintigraphic finding. Thus, we do not recommend 99mTc-DMSA for clinical use in acute lesions.